Analisis Penggunaan Deiksis Tempat dan Waktu Pada Cerpen di Surat Kabar Tempo Sebagai Bahan Ajar Bahasa Indonesia - Dewi, Kadek Indah Kusuma; Martha, I Nengah; Tantri, Ade Asih Susiari (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to describe (1) the form of place deixis in the short stories of the Tempo newspaper, (2) the form of time deixis in the short stories of the Tempo newspaper, (3) the relevance of using deixis in the short stories of the Tempo newspaper to Indonesian language learning. In achieving these objectives, researchers used a qualitative descriptive design. The subject of this research is a short story in the Tempo newspaper. The object of this research includes two things, namely the form of place deixis and the form of time deixis. In this study the data collection method used was the documentation method using data cards to sort the data obtained from the deixis of place and time. The data obtained were analyzed using a qualitative descriptive method which included five stages, namely data collection, data selection, data reduction, drawing conclusions/verification, and data presentation. The results of the analysis show that in the short stories contained in the Tempo newspaper there is a place deixis and a time deixis. The results of the analysis of place deixis and time deixis used in short stories in the Tempo newspaper found that there are two types of place deixis, namely (a) locative place deixis and (b) deixis place deixis. There are three types of time deixis, namely (a) past time deixis, (b) present time deixis, and (c) future time deixis. The results of this study are expected to be used as a means to study deixis and to make newspapers a learning medium for students through literary media, especially short stories.